2016
DOI: 10.1590/0102-6720201600040005
|View full text |Cite
|
Sign up to set email alerts
|

Do Proximal and Distal Gastric Tumours Behave Differently?

Abstract: Background: Although the incidence of gastric (adenocarcinoma) cancer has been decreasing over time, it is still one of the most common malignancies worldwide, and proximal tumours tend to have a worse prognosis. Aim: To compare surgical outcomes and prognosis between proximal - excluding tumours of the cardia - and distal gastric cancer. Methods: Out of 293 cases reviewed - 209 with distal and 69 with proximal gastric cancer - were compared for clinical and pathological features, stage, surgical outcome, mort… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 26 publications
1
17
0
Order By: Relevance
“…In this study, the results of one-way ANOVA showed P=0.066, slightly >0.05, but multivariate analysis suggested that the position of tumor is an independent risk factor. Also, analysis of results showed that patients with tumors in the upper region of stomach are more susceptible to regional lymphatic metastasis, which conforms to the results of previous studies in other countries ( 9 , 10 ). Studies have shown that regional lymphatic metastasis is one of the key risk factors leading to the postoperative recurrence and death of patients with gastric adenocarcinoma ( 11 ), which could serve as not only the prognostic indicator for development and outcome of patients, but also important evidence for stipulating the adjuvant therapy and follow-up procedure after surgery.…”
Section: Discussionsupporting
confidence: 89%
“…In this study, the results of one-way ANOVA showed P=0.066, slightly >0.05, but multivariate analysis suggested that the position of tumor is an independent risk factor. Also, analysis of results showed that patients with tumors in the upper region of stomach are more susceptible to regional lymphatic metastasis, which conforms to the results of previous studies in other countries ( 9 , 10 ). Studies have shown that regional lymphatic metastasis is one of the key risk factors leading to the postoperative recurrence and death of patients with gastric adenocarcinoma ( 11 ), which could serve as not only the prognostic indicator for development and outcome of patients, but also important evidence for stipulating the adjuvant therapy and follow-up procedure after surgery.…”
Section: Discussionsupporting
confidence: 89%
“…Researches have indicated that PGC differed from DGC in clinicopathological characteristics [1013]. For example, one previous study [11] found that PGC patients were more likely to be in an advanced tumor stage and have larger tumor size as compared to DGC.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, there was no clear agreement on the link between tumor location and overall survival (OS) of GC. Some studies [11, 1317] reported a worse prognosis in patients with PGC compared to DGC, while others [10, 12, 18] have shown no relationship between prognosis and gastric tumor location. Katsuhiko et al [19] even demonstrated that PGC patients had a longer survival time than DGC after chemotherapy.…”
Section: Introductionmentioning
confidence: 99%
“…However, the longitudinal location of the stomach tumor did not affect gastric cancer recurrence. Previously, several studies have reported on the prognosis of patients with a tumor in the proximal upper-third of the stomach compared with that in the distal region [8,[11][12][13][14][15]. Petrelli et al [14] review of 50 studies encompassing 128,268 patients with gastric cancer and tumors in the proximal upper-third of the stomach reported an increased risk of tumor-related death, suggesting that the longitudinal location of the tumor was an important stratification prognostic factor.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have investigated primary tumor location and association with gastric cancer prognosis. The results of these prior studies have been contradictory, however, with some reporting a poorer prognosis in patients with a tumor in the proximal upper-third of the stomach compared with that in the distal region [6,7], whereas other studies have indicated no relationship between prognosis and the longitudinal location of the tumor in the stomach [8]. To date, no studies have reported a definitive prognosis of proximal upper-third gastric cancer excepting cancer of the EGJ.…”
Section: Introductionmentioning
confidence: 96%